Sensitivity Improvement And Optomechanical Analysis Of Composite Material Using Fiber Bragg Grating Sensor Optomechanical Analysis of Composite Material Using Fibre Bragg Grating Sensor - Jahan M.A, Ibrar; Rajini V Honnungar, Dr.; M Upadhyaya, Anup (International Journal of Engineering and Technology, 2018)
This paper presents the design and simulation of FBG as a pressure sensor. Fiber Bragg Grating (FBG) coated with different materials and their sensitivity has been investigated. Using optomechanical equations strain and shift in wavelength values are calculated  for a bare FBG and FBG coated with PMMA, polystyrene and aluminium. Bragg wavelength/center wavelength shifts when there is perturbation on the fiber gratings due to pressure or any external change. Design parameter is achieved by FBG spectral characterization. Using R-soft and Grating –Mod tool box grating length, modulation depth, grating pitch and other physical parameters are changed and simulation is carried out. In literature various methods are proposed for sensitivity improvement. In this work from the simulation results and sensitivity calculation it was noted that FBG coated with PMMA offers good sensitivity of 1.17µm/µɛ.  Optomechanical simulation in Comsol multiphysics has also been investigated to obtain mechanical stress and strain with optical spectral response  for metal embedded FBG sensor.Remarkable shift in wavelength is observed during the analysis. Linear displacement of fibre found with respect to arc length.  Metal embedded FBG sensor is having tremendous application in aviation, automobiles,machine tools.